The Productivity of Red Chili (Capsicum annum L.) Improvement Using Inorganic Fertilizer and Biofertilizer: Implications for Sustainable Agriculture - Ade Hilman Juhaeni; Rudi Priyadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Red chili (Capsicum annum L.) is one of the important horticultural crops, yet its productivity is still relatively low. This study aims to determine the productivity of red chili improvement through the use of inorganic fertilizer and biofertilizer. The factorial randomized group design (RAK) experimental design with 2 factors and 3 replicates (10 plants for each replicate) was used in this research. Factor I consisted of four doses of inorganic fertilizer (K), namely: 200 kg/ha (k1), 300 kg/ha (k2), 400 kg/ha (k3), 500 kg/ha (k4). Factor II consists of four concentrations of biological fertilizer (H), namely: 10 ml/L (h1), 20 ml/L (h2), 30 ml/L (h3), 40 ml/L (h4). The results showed that there was no interaction effect between the use of inorganic fertilizer (NPK) and the concentration of biofertilizer (M-Bio) on fruit weight per plant (g/plant) and fruit yield per hectare (t/Ha). However, the single use of biofertilizer with a concentration of 20 ml/L significantly increased the productivity of fruit weight (555.75 g/plant or 14.81 t/Ha). Biofertilizers such as phosphate solubilizing microorganisms and nitrogen-fixing bacteria can increase the availability of macro and micro nutrients in the soil and the productivity of chili significantly. The use of biofertilizers has the benefit of reducing farmers' dependence on inorganic fertilizers. Therefore, the use of a combination of inorganic fertilizer and biofertilizer not only can be a good alternative to increase the productivity of red chili effectively and sustainably, but also to reduce the negative impact of using inorganic fertilizer on the environment.